2021
DOI: 10.3389/fonc.2021.655757
|View full text |Cite
|
Sign up to set email alerts
|

The G4 Resolvase DHX36 Possesses a Prognosis Significance and Exerts Tumour Suppressing Function Through Multiple Causal Regulations in Non-Small Cell Lung Cancer

Abstract: Lung cancer is one of the most prevalent cancers in both men and women worldwide. The nucleic acid G4 structures have been implicated in the transcriptional programmes of cancer-related genes in some cancers such as lung cancer. However, the role of the dominant G4 resolvase DHX36 in the progression of lung cancer remains unknown. In this study, by bioinformatic analysis of public datasets (TCGA and GEO), we find DHX36 is an independent prognosis indicator in non-small-cell lung carcinoma (NSCLC) with subtype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 84 publications
1
6
0
Order By: Relevance
“…The immunohistochemical data for TRIM22 was additionally included in this step to complement the results of TcoFs analysis—the gene was found to be expressed more abundantly in LUAD than in normal lungs, which could confirm its oncogenic properties in lung cancer [ 70 ]. The other interesting genes are AIFM1 , ATRX, and DHX36, which have not only various IHC data, but also the staining complements literature data on LUAD [ 91 , 95 , 96 ]. In addition, higher cancer-promoting expression is observed in patients with high AP-2δ expression, making TFAP2D a potential oncogene of lung adenocarcinoma.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The immunohistochemical data for TRIM22 was additionally included in this step to complement the results of TcoFs analysis—the gene was found to be expressed more abundantly in LUAD than in normal lungs, which could confirm its oncogenic properties in lung cancer [ 70 ]. The other interesting genes are AIFM1 , ATRX, and DHX36, which have not only various IHC data, but also the staining complements literature data on LUAD [ 91 , 95 , 96 ]. In addition, higher cancer-promoting expression is observed in patients with high AP-2δ expression, making TFAP2D a potential oncogene of lung adenocarcinoma.…”
Section: Resultssupporting
confidence: 60%
“…On the other hand, BLM or ATRX downregulation is associated with favorable events related to Non-Small Cell Lung Cancer (NSCLC) sensitization to radiotherapy or immunotherapy, respectively [ 94 , 95 ]. Finally, decreased expression of either DHX36 or ERCC3 seems to be unfavorable due to the elevated NSCLC migration and growth [ 96 ] or increased DNA adduct levels [ 97 ], even if the latter one was mainly due to ERCC5 and ERCC6 (in study by Cheng et al, the mean ERCC3 expression was lower in oncological patients but the results were not statistically significant). Additionally, the expression of TFAP2D in both the wild-type and mutated LUAD samples was compared to normal lung samples ( Figure 11 B).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that the increasing pressure of cell replication causes DNA damage and cell cycle arrest, and replicative senescence is the main cause of body aging (Go et al, 2020; Nechiporuk et al, 2016). Cyclin‐dependent kinases (CDKs) are critical regulators of replicative senescence procession (Cui et al, 2021; Gao et al, 2016; Misono et al, 2019). Furthermore, P21 and P16 are key genes involved in the regulation of CDKs, and their expression levels have been used as important reference indexes in related anti‐aging studies (Chu et al, 2017; Rasool et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, numerous G4 structures found in the human genome and mRNA indicate that G4 and its major resolvase, RHAU, played important roles in regulating gene transcription and translation 51,52 . Previous studies have found that RHAU has an inhibitory effect on the tumorigenesis of lung cancer and breast cancer 53–55 . However, the role of RHAU under these disease conditions remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%